Między gloryfikacją a szyderstwem. Rola odwołań historycznych w memach internetowych = Between glorification and mockery. The role of references to history in Internet memes - Niekrewicz, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to discuss the manner of presenting historical events and figures in memes, as well as evaluation which is present in the language, image and text of memetic utterances. The subject of the analysis is 1000 Polish-language memes which were published - usually multiple times - on the most popular websites.
Keywords: mem internetowy; historia; wartościowanie; deprecjacja; gry intertekstualne; internet meme; history; language evaluation; depreciation; intertextual games